2002
DOI: 10.1128/jb.184.14.3941-3946.2002
|View full text |Cite
|
Sign up to set email alerts
|

An AraC/XylS Family Member at a High Level in a Hierarchy of Regulators for Phenol-Metabolizing Enzymes inComamonas testosteroniR5

Abstract: Comamonas testosteroni strain R5 expresses a higher level of phenol-oxygenating activity than any other bacterial strain so far characterized. The expression of the operon encoding multicomponent phenol hydroxylase (mPH), which is responsible for the phenol-oxygenating activity, is controlled by two transcriptional regulators, PhcS and PhcR, in strain R5. In this study, we identified a third transcriptional regulator for the mPH operon (PhcT) that belongs to the AraC/XylS family. While the disruption of phcT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Similar binding motifs were also found in the putative IHF-binding site of the phcR - phcK intergenic region [28]. Hence, it is suggested that these proteins could bind to the putative IHF binding sites and hamper the binding of IHF [15], [28], [48]. However, the IHF-binding consensus motif is absent in the A+T-rich sequence of the mph operon of strain PHEA-2.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Similar binding motifs were also found in the putative IHF-binding site of the phcR - phcK intergenic region [28]. Hence, it is suggested that these proteins could bind to the putative IHF binding sites and hamper the binding of IHF [15], [28], [48]. However, the IHF-binding consensus motif is absent in the A+T-rich sequence of the mph operon of strain PHEA-2.…”
Section: Discussionmentioning
confidence: 53%
“…One of the AphS binding sites (consensus motif, TATCGTAT) determined by gel-mobility shift assay is located around the putative IHF (Integration Host Factor)-binding site, but not within the putative UASs [7]. Similar binding motifs were also found in the putative IHF-binding site of the phcR - phcK intergenic region [28]. Hence, it is suggested that these proteins could bind to the putative IHF binding sites and hamper the binding of IHF [15], [28], [48].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This third regulator, designated PhcT, belongs to the AraC/XylS-type regulators and was found to stimulate the expression of genes involved in phenol catabolism in the presence of the main PhcR activator (Teramoto, Ohnishi, Harayama, & Watanabe, 2002).…”
Section: Common Transcriptional Regulation Of a Peripheral And A Centmentioning
confidence: 99%
“…Another example is provided by the phcT regulatory gene. PhcT is at the top of a regulatory cascade controlling phenol degradation (250). PhcT enhances transcriptional activation of the phc operon for phenol degra- …”
Section: Mechanism Of Transcription Activationmentioning
confidence: 99%